Marine algal flora of Flores and Corvo Islands, Azores - Neto, Ana I. (2021)
BACKGROUND The algal flora of the western group of the Azores archipelago (Islands of Flores and Corvo) has attracted the interest of many researchers on numerous past occasions (such as Drouet 1866, Trelease 1897, Gain 1914, Schmidt 1929, Schmidt 1931, Azevedo et al. 1990, Fralick and Hehre 1990, Neto and Azevedo 1990, Neto and Baldwin 1990, Neto 1996, Neto 1997, Neto 1999, Tittley and Neto 1996, Tittley and Neto 2000, Tittley and Neto 2005, Tittley and Neto 2006, Azevedo 1998, Azevedo 1999, Tittley et al. 1998, Dionísio et al. 2008, Neto et al. 2008). Despite this interest, the macroalgal flora of the Islands cannot be described as well-known with the published information reflecting limited collections preformed in short-term visits by scientists. To overcome this, a thorough investigation, encompassing collections and presence data recording, has been undertaken for both the littoral and sublittoral regions, down to a depth of approximately 40 m, covering a relatively large area on both Islands (approximately 143 km² for Flores and 17 km² for Corvo). This paper lists the resultant taxonomic records and provides information on species ecology and occurrence around both these Islands, thereby improving the knowledge of the Azorean macroalgal flora at both local and regional scales. NEW INFORMATION For the Island of Flores, a total of 1687 specimens (including some taxa identified only to genus level) belonging to 196 taxa of macroalgae are registered, comprising 120 Rhodophyta, 35 Chlorophyta and 41 Ochrophyta (Phaeophyceae). Of these taxa, 128 were identified to species level (80 Rhodophyta, 22 Chlorophyta and 26 Ochrophyta), encompassing 37 new records for the Island (20 Rhodophyta, 6 Chlorophyta and 11 Ochrophyta); two Macaronesian endemics (Laurencia viridis Gil-Rodríguez & Haroun and Millerella tinerfensis (Seoane-Camba) S.M.Boo & J.M.Rico); six introduced (the Rhodophyta Asparagopsis armata Harvey, Neoizziella divaricata (C.K.Tseng) S.-M.Lin, S.-Y.Yang & Huisman and Symphyocladia marchantioides (Harvey) Falkenberg; the Chlorophyta Codium fragile subsp. fragile (Suringar) Hariot; and the Ochrophyta Hydroclathrus tilesii (Endlicher) Santiañez & M.J.Wynne and Papenfussiella kuromo (Yendo) Inagaki); and 14 species of uncertain status (10 Rhodophyta, two Chlorophyta and two Ochrophyta). For the Island of Corvo, a total of 390 specimens distributed in 56 taxa of macroalgae are registered, comprising 30 Rhodophyta, nine Chlorophyta and 17 Ochrophyta (Phaeophyceae). Whilst a number of taxa were identified only to the genus level, 43 were identified to species level (22 Rhodophyta, eight Chlorophyta and 13 Ochrophyta), comprising 22 new records for the Island (nine Rhodophyta, four Chlorophyta and nine Ochrophyta), two introduced species (the Rhodophyta Asparagopsis armata and the Chlorophyta Codium fragile subsp. fragile and seven species of uncertain status (five Rhodophyta and two Ochrophyta).